PENGEMBANGAN BAHAN AJAR MATERI ENTREPRENURERSHIP BERBASIS INTERNET MARKETING - Alif Ringga Persada (EduMa: Mathematics education learning and teaching, 2017)
Student skill of concerning entrepreneurship still need the existence of improvement in order to become better again. Technological growth make the disrupted in running kewirausahaan so that need the skill entrepreneurship base on the internet marketing. this Research target is make the teaching material the entrepreneurship base on the internet marketing which valid. Research method used by is research and development with the model of development ADDIE covering step Analysis, Design, Development, Impelementation And Evaluation. Result of research and development is teaching material the entrepreneurship base on the internet marketing which have valid by expert. Response Student to teaching material the entrepreneurship with the mean 66%. mean Pretes of equal to 58,55 and postes 83,55. Pursuant to test of paired sampel t-test known by the existence of difference of result of learning which signifikan to teaching material the entrepreneurship base on the internet marketing.Keyword: Material Learning, Entrepreneurship, Internet Marketing